Optimization of the mechanical properties of CNTs/Cu composite by regulating the size of interfacial TiC. Issue 18 (15th September 2022) - Feng, Junqin; Tao, Jingmei; Liu, Yichu; Bao, Rui; Li, Fengxian; Fang, Dong; Li, Caiju; Yi, Jianhong
Abstract: The formation of interfacial carbides by in-situ reaction is a valid way to improve the interfacial bonding strength and mechanical performance of metal matrix composites. In this study, Cu matrix composites reinforced by carbon nanotubes (CNTs) were fabricated by molecular level mixing (MLM) combined with subsequent powder metallurgy (PM) to obtain the interfacial TiC with suitable size. In contrast to typical PM, CNTs were homogeneously distributed and partially incorporated in Cu matrix in the composite powders prepared by MLM, which was a critical factor in generating nanoscale interfacial TiC. The TiC nanoparticles can not only adhere firmly to CNTs, but also form semi-coherent interfaces with Cu matrix, thus achieving strong interface bonding by bridging the gaps between them. The ultimate tensile strength of the prepared composite is as high as 364 MPa with a CNTs content of 0.8 vol% and a noticeable strengthening efficiency of 206, which is considered to be the full exertion of load-transfer. This work can provide a novel perspective for the fabrication of CNTs/Cu composites by introducing nanosized interfacial carbides to improve the mechanical properties.